Business Process Improvement Approach in Vehicle Facility Application System: A Case Study at PT Unggul Lancar Sejahtera (ULS) - Wazaumi, Dwi Diana; Fahriel Dwifaldi (Journal of Advances in Information and Industrial Technology, 2026)
Deadlock incidents in the vehicle facility application system at PT Unggul Lancar Sejahtera (ULS) caused significant operational delays, with cycle time efficiency as low as 2.02% and frequent manual interventions. This study addresses the problem using the Business Process Improvement (BPI) approach to redesign workflows and eliminate bottlenecks. The proposed solution integrates BPI analysis with the deployment of a Hangfire-based workflow engine, enabling automatic retry mechanisms and process monitoring. The methodology involved identifying NonValue Added (NVA) activities, restructuring approval flows, and implementing automation to improve transparency and reduce downtime. The research contributes a practical model for process improvement that combines structured BPI analysis with modern workflow orchestration tools. Results show a substantial improvement, with deadlock-handling time reduced from 120 minutes to 0.32 minutes and cycle-time efficiency increasing to 93.99%. Compared to existing manual resolution methods, the proposed approach offers higher reliability, faster recovery, and enhanced visibility, providing a replicable framework for organizations facing similar workflow inefficiencies.